2019
DOI: 10.1002/jaba.626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of language on behavior treatment outcomes

Abstract: Resurgence of problem behavior following effective functional communication training (FCT) can occur if the functional communication response contacts extinction. For children from duallanguage households, extinction may unintentionally occur due to language variations among communication partners. In the current study, the experimenters evaluated the effect of language on FCT outcomes. Participants were 3 children with autism who engaged in problem behavior and whose parents reported Spanish as the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…For example, differential reinforcement of alternative behavior (DRA) or functional communication training (FCT) are effective treatments for problem behavior, but resurgence of problem behavior occurs when reinforcement for the alternative response is disrupted (e.g., Gratz, Wilson, & Glassford, 2019;Hoffman & Falcomata, 2014;Lieving, Hagopian, Long, & O'Connor, 2004;Marstellar & St. Peter, 2014;Neely, Graber, Kunnavatana, & Cantrell, 2019;Volkert, Lerman, Call, & Trosclair-Lasserre, 2009;Wacker et al, 2013). Behavioral treatments are effective for producing initial reductions in problem behavior; however, relapse after treatment is common and a major barrier to treatment efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, differential reinforcement of alternative behavior (DRA) or functional communication training (FCT) are effective treatments for problem behavior, but resurgence of problem behavior occurs when reinforcement for the alternative response is disrupted (e.g., Gratz, Wilson, & Glassford, 2019;Hoffman & Falcomata, 2014;Lieving, Hagopian, Long, & O'Connor, 2004;Marstellar & St. Peter, 2014;Neely, Graber, Kunnavatana, & Cantrell, 2019;Volkert, Lerman, Call, & Trosclair-Lasserre, 2009;Wacker et al, 2013). Behavioral treatments are effective for producing initial reductions in problem behavior; however, relapse after treatment is common and a major barrier to treatment efficacy.…”
mentioning
confidence: 99%
“…Behavioral treatments are effective for producing initial reductions in problem behavior; however, relapse after treatment is common and a major barrier to treatment efficacy. For example, differential reinforcement of alternative behavior (DRA) or functional communication training (FCT) are effective treatments for problem behavior, but resurgence of problem behavior occurs when reinforcement for the alternative response is disrupted (e.g., Gratz, Wilson, & Glassford, 2019;Hoffman & Falcomata, 2014;Lieving, Hagopian, Long, & O'Connor, 2004;Marstellar & St. Peter, 2014;Neely, Graber, Kunnavatana, & Cantrell, 2019;Volkert, Lerman, Call, & Trosclair-Lasserre, 2009;Wacker et al, 2013). Most research into relapse processes in clinical settings attempts to translate methods developed in studies of extinction learning (e.g., Liddon, Kelley, Rey, Liggett, & Ribeiro, 2018), even though extinction alone is rarely used as a technique to eliminate behavior in clinical settings.…”
mentioning
confidence: 99%
“…Resurgence is the recurrence of a previously eliminated response when reinforcement for an alternative is disrupted or worsened (Lattal et al, 2017). Relevant to the findings of Neely, Graber et al (2020), children with communication needs from CLD families may contact verbal communities who either exclusively reinforce communication in one language (e.g., the language at home) or another (e.g., the language at school). For these children, teaching mands in one language (e.g., English) only empowers them to recruit reinforcement in a subset of relevant environments (e.g., school) but not others (e.g., home).…”
mentioning
confidence: 79%
“…The child engaged in more correct responding and lower percentages of challenging behavior when instruction was delivered in the home language (i.e., Spanish). Similarly, Neely, Graber et al (2020) observed that the acquisition of mands following FCT in English‐only contexts rarely generalized to Spanish‐only contexts. Moreover, challenging behavior resurged in the Spanish‐only contexts when English mands were not reinforced, which adds to the body of research showing resurgence during unsignaled extinction of mands following FCT (e.g., Briggs et al, 2018; Greer & Shahan, 2019; Hoffman & Falcomata, 2014; Lambert et al, 2016, 2017; Peterson et al, 2017; Pritchard et al, 2014; Schmitz et al, 2019; Wacker et al, 2013).…”
mentioning
confidence: 92%
“…Research in this domain is particularly relevant to Latinx consumers who either live in multilingual households or for whom English is not their primary language. Studies examining the effects of language on discrete-trial instruction (Lang et al, 2011 ), the acquisition of play skills (Lim & Charlop, 2018 ), the recovery of extinguished problem behavior following functional communication training (Neely et al, 2020 ; Padilla Dalmau et al, 2011 ), and assessments of behavior function (Rispoli et al, 2011 ) have demonstrated that the language used during instruction or assessment can have important effects on the outcomes obtained. Multilingual situations present unique challenges for behavior-analytic practitioners, as the language required for the important social interactions taking place in the home may not be the language consumers need to use and respond to in other settings (e.g., school, workplace, community).…”
Section: Cultural and Language Adaptations To Evidence-based Treatmentsmentioning
confidence: 99%